BIMBINGAN PERKAWINAN CALON PENGANTIN UNTUK MEWUJUDKAN KELUARGA SEJAHTERA DI KUA KECAMATAN BANGSALSARI JEMBER - Thariq Abdul Aziz; Samsul Arifin; Ach. Zukin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2025)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal home based on the Almighty Godhead. The aim of this research is to describe marriage guidance for prospective brides and grooms to create a prosperous family at the Bangsalsari District Religious Affairs Office, Jember Regency. This research uses a qualitative research method with a case study type of research. The results of research on marriage guidance for prospective brides and grooms to create a prosperous family consist of seven stages, namely the first is preparation, the prospective bride and groom prepares the documents to register and the counselor prepares the material to be delivered, the second the prospective bride and groom communicate directly with the counselor, the third the prospective bride and groom tell the problems- problems faced, the four prospective brides and grooms interact with counselors to introduce themselves and get to know each other's characters, the fifth conference is related to solving the problems experienced by the prospective brides and grooms, the sixth goal setter at this stage the prospective brides and grooms can respond to the problems faced and can establish a home life and The seventh is the final action taken after carrying out the previous stages. The advisor hopes that by providing useful advice to each participant, they can build a good home life and create a prosperous family.